Adolescents and adults affected by Cornelia de Lange syndrome: A report of 73 Italian patients. Issue 2 (10th May 2016) - Mariani, Milena; Decimi, Valentina; Bettini, Laura Rachele; Maitz, Silvia; Gervasini, Cristina; Masciadri, Maura; Ajmone, Paola; Kullman, Gaia; Dinelli, Marco; Panceri, Roberto; Cereda, Anna; Selicorni, Angelo
Abstract : Cornelia de Lange syndrome (CdLS) is a rare genetic condition related to mutation of various cohesion complex related genes. Its natural history is quite well characterized as regard pediatric age. Relatively little information is available regarding the evolution of the disease in young‐adult age. In medical literature, only one specific study has been published on this topic. We report on our experience on 73 Italian CdLS patients (40 males and 33 females) with and age range from 15 to 49 years. Our results confirm the previous study indicating that gastroesophageal reflux disease (GERD) is the main medical problem of these patients in childhood and young‐adult age. Other medical features that should be considered in the medical follow‐up are tendency to overweight/frank obesity, constipation, discrepancy of limbs' length, epilepsy, hearing, and visual problems. Behavioral problems are particularly frequent as well. For this reason, every source of hidden pain should be actively searched for in evaluating a patient showing such a disorder. Finally, recommendations for medical follow‐up in adult age are discussed. © 2016 Wiley Periodicals, Inc.